Improving University Quality of Services through Mobile Devices: The Case of the Technological University of Panama - Muñoz, Lilia; Villarreal, Vladimir; Sanchez, Alex (My University)
Society evolves at a rapid pace, integrates the latest everydays life technologies and squeezes the benefits of innovation. At the same time, universities follow these same steps, creating great possibilities by providing better services and formation as the result of this evolution. In this sense, mobile devices have become an instrument that allows a new way of interacting with the university services. This article describes the development of an apptool called “UTPMovil”. This tool allows access to the University general information, as well as events, book consultation, schedules and others. “UTPMovil” has been developed for the Android platform. This project seeks to be at the forefront of technology hence providing a tool, using mobile devices, for the use of students, teachers and administrators of the Technological University of Panama.
Society evolves at a rapid pace, integrates the latest everydays life technologies and squeezes the benefits of innovation. At the same time, universities follow these same steps, creating great possibilities by providing better services and formation as the result of this evolution. In this sense, mobile devices have become an instrument that allows a new way of interacting with the university services. This article describes the development of an apptool called “UTPMovil”. This tool allows access to the University general information, as well as events, book consultation, schedules and others. “UTPMovil” has been developed for the Android platform. This project seeks to be at the forefront of technology hence providing a tool, using mobile devices, for the use of students, teachers and administrators of the Technological University of Panama.
Keywords: web services; software development; human computer interaction; mobile users interfaces design; web services; software development; human computer interaction; mobile users interfaces design